Reindustrializing Indonesia: Human Capital, Innovation, and Entrepreneurial Growth in a Changing Industrial Landscape - Pramanda, Ryan (Journal of Economic Growth and Development Review, 2025)
As emerging economies grapple with post-pandemic recovery and long-term development challenges, the call to "reindustrialize" has gained renewed attention. This paper examines how human capital, technological innovation, and entrepreneurship function as core drivers of industrial transformation, using Indonesia as a case example. Drawing on literature review and policy analysis, it highlights how workforce readiness, innovation ecosystems, and entrepreneurial infrastructure interact within national strategies. While Indonesia has launched bold initiatives in industrial downstreaming, vocational education, and SME digitization, its efforts are constrained by institutional fragmentation, skills mismatches, and uneven regional development. The study argues that successful reindustrialization in emerging economies requires an integrated, people-centered approach one that connects talent with technology and local innovation with global competitiveness. It concludes by offering policy recommendations to align human development, technological capability, and entrepreneurship in support of sustainable and inclusive industrial growth